2016
DOI: 10.1002/bjs.10183
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with colonic carcinoma before, during and after implementation of complete mesocolic excision

Abstract: With CME, the quality indicators of process and outcome quality improved, especially in stage III colonic carcinoma. Adjuvant chemotherapy in stage III and multidisciplinary approaches in patients with metachronous distant metastases contributed to further outcome improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 25 publications
7
82
3
3
Order By: Relevance
“…The Hohenberger et al . study updated its data in 2016, and we selected the updated study . Finally, 12 studies with 8586 patients (3610 in the CME group and 4976 in the NCME group) were included in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Hohenberger et al . study updated its data in 2016, and we selected the updated study . Finally, 12 studies with 8586 patients (3610 in the CME group and 4976 in the NCME group) were included in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies described safety outcomes (Table ). CME was associated with more intra‐operative blood loss (WMD 79.87, 95% CI: 65.88–93.86) and postoperative surgical complications (RR 1.23, 95% CI: 1.08–1.40) than NCME.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Hohenberger et al 59 published a paper arguing for an increased focus on standardized surgical techniques for colon cancer. In a recent paper by Merkel et al, 60 they showed that 5-year cancer-related survival rate increased from 61% to 80%. This survival improvement corresponds with the nationwide implementation of CME.…”
Section: The Future Of Tailored Crc Treatmentmentioning
confidence: 97%